Nursing care of a patient with erectile dysfunction after myocardial infarction – case study - Tkaczyk, Filip M.; Siudak, Zbigniew (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Erectile dysfunction after myocardial infarction can have a variety of aetiologies, associated with damage to the blood vessels and nerves responsible for normal penile erection, stress, fatigue, endocrine disruption, side effects of pharmacotherapy, and psychiatric disorders. The aim of this study is to provide knowledge and insight into the nursing care of a patient with erectile dysfunction after myocardial infarction. The study used a case study research method, including a description of the patient’s condition, aiming at its in-depth analysis and evaluation. The C-HOBIC care outcome indicators were used in the case description. ICNP® reference terminology was used for the nursing process. Nursing care of patients with erectile dysfunction after myocardial infarction incorporates a holistic approach that addresses both physical and psychosocial aspects.